Class voice fundamental skills for lifelong singing - Smith, Brenda (Brenda Jo); Burrichter, Ronald (Plural Publishing Inc., 2023)
Class Voice: Fundamental Skills for Lifelong Singing is a unique undergraduate textbook which can be adapted to needs of any potential voice user, including music education students, voice students who are not majoring in music, and adult learners. By explaining the basics of singing using practical skills and examples, this text is accessible to students with a wide range of talents, interests, and expertise levels. With chapters devoted to skills for singing solo and in groups, instructors can tailor the included materials to encourage students to become thoroughly familiar with their own voices and to identify and appreciate the gifts of others"--